Course and predicting factors of lower-extremity injuries after running a marathon - van Middelkoop, M.; Kolkman, J.; van Ochten, J.; Bierma-Zeinstra, S. M. A.; Koes, B. W. (Clinical Journal of Sport Medicine, 2007)
Abstract: Objectives: To investigate in recreational runners the 3 month prognosis of and medical consumption caused by running injuries occurring shortly before or during a marathon. Possible prognostic factors for persistent complaints were also evaluated.